Discovering students’ strategies in learning English online / Kamisah Ariffin, Norhajawati Abdul Halim and Norizul Azida Darus - Ariffin, Kamisah; Abdul Halim, Norhajawati; Darus, Norizul Azida (Universiti Teknologi MARA, 2021)
Online learning poses challenges that students might never have encountered in a face-to-face learning environment. In learning English, students may confront more challenges as they need both cognitive and metacognitive skills in dealing with the dynamic lessons involving interaction, online exercises, and audio, video and text downloads. The challenges faced in online learning have led students to employ learning strategies to help them learn more efficiently and effectively. This paper examined students’ strategy use in learning English online and the correlation of the strategies with their academic performance in the subject. Using the Online Language Learning Strategy Questionnaire (OLLSQ) to gauge students’ strategy use in the domains of cognitive, metacognitive, resource-management and affective, the findings indicated that all students were high users of OLLS in English online learning with the highest preference for metacognitive as the strategies were helpful to students in planning and organizing their studies. However, there was low correlation between the strategies use and performance. Overall, the strategies have impacted the students positively and helped them to cope with the new learning mode that is different from the traditional learning. It is hoped that the discovery of the strategies could provide some important insights into how students can be more successful in learning online, and help others to achieve their study goals and overcome any challenges confronting them in learning English online.